Potential of bacterial fermentation as a biosafe method of improving feeds for pigs and poultry - A. T. Niba; J. D. Beal; A. C. Kudi; P. H. Brooks (African Journal of Pig Farming, 2009)
The use of fermented liquid feeds in monogastric animal nutrition is regarded as one of the biosafe methods of animal production. This paper examines bacterial fermentation of feed substrates for production of fermented liquid feeds for pigs and moist feeds for poultry. Emphasis is placed on the interplay of factors affecting feed fermentation and their relationship to feed quality. The resistance of fermented feeds to enteropathogenic contamination prior to feeding and their potential contribution to African agriculture is highlighted.